O encanto de fazer poesias livres - Fernandes, Marta Oliveira Cordeiro; Feijó, Giane Felix; Ribeiro, Onevan da Silva; Bordinhão, Andréia Jonceline Chiozini; Simião, Regina Aparecida Versoza (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf